Analyses of the genotoxic and mutagenic potential of the products formed after the biotransformation of the azo dye Disperse Red 1 - Drumond Chequer, Farah Maria; Lizier, Thiago Mescoloto [UNESP]; de Felicio, Rafael; Zanoni, Maria Valnice Boldrin [UNESP]; Debonsi, Hosana Maria; Lopes, Norberto Peporine; Marcos, Ricard; de Oliveira, Danielle Palma (Pergamon-Elsevier B.V. Ltd, 2011)
Azo dyes constitute the largest class of synthetic dyes. Following oral exposure, these dyes can be reduced to aromatic amines by the intestinal microflora or liver enzymes. This work identified the products formed after oxidation and reduction of the dye Disperse Red 1, simulating hepatic biotransformation and evaluated the mutagenic potential of the resultant solution. Controlled potential electrolysis was carried out on dye solution using a Potentiostat/Galvanostat. HPLC-DAD and GC/MS were used to determine the products generated after the oxidation/reduction process. The Salmonella/microsome assay with the strains TA98 and YG1041 without 59, and the mouse lymphoma assay (MLA) using the thymidine kinase (Tk) gene, were used to evaluate the mutagenicity of the products formed. Sulfate 2-[(4-aminophenyl)ethylaminol-ethanol monohydrate, nitrobenzene, 4-nitro-benzamine and 2-(ethylphenylamino)-ethanol were detected. This dye has already being assigned as mutagenic in different cell system. In addition, after the oxidation/reduction process the dye still had mutagenic activity for the Salmonella/microsome assay. Nevertheless, both the original dye Disperse Red 1 and its treated solutions showed negative results in the MLA. The present results suggest that the ingestion of water and food contaminated with this dye may represent human and environmental health problem, due to the generation of harmful compounds after biotransformation. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Azo dye; Disperse Red 1; Biotransformation; Mutagenicity; Ames test; Mouse lymphoma assay